Responsabilidad social ambiental de las empresas del sector maderero en la ciudad de Armenia (2012)
In the Armenia Quindío city has problems because of high levels of pollution, this can create problems of various kinds. Thus is denoted timely making research to measure the degree of commitment to one of most controversial and destructive sectors of the city of Armenia, such as is the wood sector. Thus, to obtain valuable information on the matter specified end of the investigation, its results and a series of recommendations for correcting the problem Because of the problems that currently are denoted regarding treatment of social responsibility, is to determine what level of commitment, social- environmental responsibility of wood sector engaged in transforming this material versus environment.